Listening for God with the Third Ear - Alling, Frederic A. (Journal of religion and health, 2000)
There are similarities between the way a psychotherapist listens for messages from a patient's (or client's) unconscious and the way a spiritual person listens for messages from God. In this paper I describe three pathways or channels through which messages are heard by both listeners: recurrent patterns, dissonant notes, and dreams. Examples are given to illustrate the listening techniques used by the therapist listener and the religious listener to hear messages from transcendent realms. Not only the names, but some of the descriptive information in these examples, have been changed to protect the privacy of those who have shared their listening experiences with me.